Chronic effects of fire suppressors on the reproduction of the copepod Nitocra sp. - Ueda-De-Carvalho, Maysa [UNESP]; Buruaem-Moreira, Lucas [UNESP]; Maranho, Luciane Alves; Moledo-de-Souza-Abessa, Denis [UNESP] (Univ Narino, 2019)
Fire suppressors are widely used in firefighting and their chemical composition may present a mixture of perfluorochlorinated surfactants (PFCs), including the perfluorooctane sulfonate (PFOS) which has been internationally banned due to its classification as a persistent organic pollutant (POP). PFCs have been found in environmental matrices and soft tissues of organisms, but the potential effect of such compounds on marine organisms has been overlooked. Here, it was evaluated whether the chronic exposures (i.e., seven days) to the fire suppressors Ageofoam, Cold Fire, Kidde and Argus could affect the reproduction of the copepod Nitocra sp. The tested concentrations consisted of those recommended on the products' manuals and those ranging between 0.0001% and 1%. For each compound, the effective concentrations to 50% exposed organisms (EC50) and the lowest observed effect concentrations (LOEC) were estimated. All the fire suppressors exhibited high toxicity, causing fecundity reduction. At the recommended dilutions, 100% lethality occurred for all compounds. The EC50 values ranged from 0.00817% - Ageofoam - to 0.03081% - Argus. The LOECs ranged from 0.001% - Ageofoam - to 0.1% Argus and Kidde; and were much lower than the concentrations recommended for commercial use. The fire suppressors showed high toxicity to the copepod, reducing the reproduction rates, even in very low concentrations, suggesting that the release of such substances in the estuary caused severe effects to the environment. This assessment provides subsides to the environmental regulation of fire suppressors in Brazil, because these compounds do not have national regulations for their use and disposal.
Keywords: ecotoxicology; aquatic organisms; pollutants; surfactants